An additive for coating lithium battery positive electrode material and preparation method thereof

The surface coating of the positive electrode material of the lithium-ion battery is solved by the LiaMgbMec (PO4)dYe additive, which solves the problems of high total alkali residue, poor high voltage stability and active lithium consumption of the positive electrode material, and achieves higher battery performance and safety.

CN119750531APending Publication Date: 2025-04-04华鼎国联动力电池有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411957324.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

There is currently no overall solution to the problems of high total alkali residues in the positive electrode material of lithium-ion batteries, poor high voltage stability, and long cycles.

Method used

The surface coating is carried out using LiaMgbMec (PO4)dYe additive and prepared by ball milling, sintering and spray drying to improve the high voltage stability and cycling performance of the positive electrode material.

Benefits of technology

Effectively reduce the total alkali residue of the positive electrode material, improve high voltage stability and cycling performance, reduce active lithium consumption, and improve Li+ conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750531A_ABST
    Figure CN119750531A_ABST
Patent Text Reader

Abstract

The present invention relates to an additive for coating anode materials of lithium batteries and a preparation method thereof. The main components of the additive are: Li a Mg b Me c (PO4) d Y e , wherein Me represents the doped transition metal element, and Y represents the anion; wherein a is 0<a≤1.5, b is 0<b≤1, c is 0≤c≤0.2, d is 0<d≤1, and e is 0≤e≤0.2; as an additive for coating lithium battery positive electrode materials, it can reduce the residual alkali of lithium battery positive electrode materials and improve high voltage stability; to a certain extent, as a lithium supplement additive, it can improve the high temperature safety and cycle stability of lithium battery positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an additive for coating anode materials of lithium batteries and a preparation method thereof, as well as application in cathode materials. Background Art

[0002] The performance of positive electrode materials directly affects the performance indicators of lithium batteries, so they occupy a core position in lithium batteries. Excessive residual alkali content on the surface of positive electrode materials will have many negative effects on electrochemical performance. The presence of residual alkali will not only deteriorate the electrochemical performance, but also cause the generation of gases such as CO, CO2 and O2 during the electrochemical reaction; the release of a large amount of gas will cause the battery to swell and affect its safety performance; and the gas production process will release heat, causing the internal temperature of the battery to rise, triggering thermal runaway, and causing the performance of the positive electrode material to decline; in severe cases, it may cause the battery to spontaneously combust, threatening safety issues.

[0003] In addition, a long-term challenge facing lithium-ion batteries is the consumption of active lithium and the formation of SEI (solid electrolyte interface), which will lead to irreversible lithium loss in the initial cycle and gradually further deplete the active lithium in subsequent cycles; in recent years, positive electrode lithium replenishment technology has begun to attract people's attention and research; positive electrode lithium replenishment is achieved by adding lithium replenishment materials to the positive electrode of the lithium-ion battery. During the battery charging process, the lithium replenishment materials decompose and release active lithium, which compensates for the irreversible active lithium loss caused by the growth of SEI at the negative electrode.

[0004] In view of the problems of high total alkali residue, poor high voltage stability and active lithium consumption caused by long cycle in traditional lithium-ion cathode materials, it is crucial to develop high-safety and low-cost lithium replenishment technology to improve the energy density and cycle life of lithium-ion batteries. In recent years, a variety of cathode materials have been developed.

[0005] For example, Chinese patent CN118419984A discloses a positive electrode lithium supplement additive, which can effectively isolate Li by coating a transition metal oxide layer on a lithium-rich transition metal oxide core. + Direct contact with the environment reduces the amount of residual alkali on the surface of the material, thereby significantly reducing the agglomeration of the slurry during the homogenization process, thereby reducing the difficulty of manufacturing.

[0006] For example, Chinese patent CN114220951B discloses a positive electrode lithium supplement additive and preparation method, a positive electrode sheet and a lithium ion battery, comprising a core material and an outer layer material coated on at least a part of the outer surface of the core material, wherein the core material is a lithium oxide, and the outer layer material is a lithium compound, wherein the lithium compound contains non-metallic elements, and the non-metallic elements include one or more of phosphorus, sulfur or selenium. It has a higher specific capacity and more lithium desorption potential, making it easier for lithium ions to be embedded and de-embedded, better conductivity, and better lithium supplementation effect.

[0007] For example, Chinese patent CN118738357A discloses a high-nickel ternary positive electrode material with low residual alkali, high specific capacity, and high cycle stability and a preparation method thereof. The prepared high-nickel ternary positive electrode material includes a molecular formula of LiNi x Co y Mn z The active material of O2 (0.8≤x<1, 0<y<<0.2, 0<z<0.2, and x+y+z=1), and the coating layer formed by primary co-coating of aluminum phosphate and lithium phosphate and secondary coating of graphene, carbon nanotubes and conductive carbon black composite coating agent can effectively reduce the residual alkali content in the high-nickel ternary positive electrode material, and at the same time improve the conductivity of the high-nickel ternary positive electrode material, thereby significantly improving its specific capacity and cycle stability.

[0008] For example, Chinese patent CN118763207A provides a coated modified positive electrode material, which comprises a substrate containing lithium nickel manganese oxide and a coating layer coated on at least part of the surface of the substrate, and its chemical formula is Li x Al y Ti z O x / 2+3y / 2+2z , 0.8<x<1.1, 0.9<y<1.1, 0.9<z<1.1. The provided coated modified positive electrode material can effectively isolate the electrolyte, protect the substrate from HF corrosion, and improve the electrochemical cycle performance of the positive electrode material; the lithium aluminum titanate material can also improve the ionic conductivity and electronic conductivity of the positive electrode material, effectively reduce the capacity attenuation and impedance increase during the cycle process, improve the cycle performance of the material, and improve the rate performance of the positive electrode material.

[0009] However, the above technical solutions only solve part of the problems separately. There is no overall solution to the problems of high total alkali residue, high temperature stability, and active lithium consumption caused by long cycles in lithium battery positive electrode materials. Here, the present invention provides a method for preparing an additive for coating lithium battery positive electrode materials, which can improve high voltage stability, reduce total alkali residue in positive electrode materials, and consume active lithium caused by long cycles through surface coating. Summary of the invention

[0010] In view of this, the object of the present invention is to provide an additive for coating anode materials of lithium batteries, the additive comprising the main components: Li a Mg b Me c (PO4) d Y e , where Me represents the doping transition metal element and Y represents the anion;

[0011] Where a is 0<a≤1.5, b is 0<b≤1, c is 0≤c≤0.4, d is 0<d≤1, and e is 0≤e≤0.4;

[0012] The number of Me cations present is greater than or equal to 0;

[0013] The number of Y anions present is greater than or equal to 0.

[0014] Among them, the Me-doped transition metal element includes but is not limited to one or more elements of Al, V, Co, Cu, Nb, Mo, and Ti; preferably, the Me-doped transition metal element is one or more elements of Al, Nb, Ti, and Mo.

[0015] Wherein, the Y anion includes Cl - 、F - 、NO3 - 、SO3 2- 、SO4 2- 、S2O8 2- 、SiO3 2- PO4 3- PO3 3- 、P2O7 4- At least one of; Preferably, the anion of Y includes F - PO4 3- PO3 3- 、P2O7 4- One or more of .

[0016] Further, in the additive, 0.6≤a≤1.5, 0.5≤b≤1.0, 0.05≤c≤0.3, 0.5≤d≤1.0, 0.05≤c≤0.3;

[0017] Furthermore, in the additive, 0.8≤a≤1.3, 0.8≤b≤1.0, 0.1≤c≤0.2, 0.8≤d≤1.0, 0.1≤c≤0.2.

[0018] The preparation method of the additive for coating the positive electrode material of a lithium battery may include the following steps:

[0019] S1: mixing the lithium source, magnesium source, Me source and phosphorus source in proportion by using a ball mill to obtain a first mixture;

[0020] S2: Sinter the first mixture to obtain a sintered product Li a Mg b Me c (PO4) d Y e additive;

[0021] S3: Add the obtained sintered product to a dispersant, mix by ball milling (in a ball mill), and obtain the obtained slurry by spray drying and sieving to obtain an additive powder.

[0022] Wherein, the lithium source is one or any combination of lithium carbonate, lithium nitrate, lithium acetate, lithium chloride, lithium hydroxide, lithium fluoride, and lithium phosphate; preferably, the lithium source is one or any combination of lithium carbonate, lithium acetate, lithium hydroxide, and lithium fluoride;

[0023] Wherein, the magnesium source is one or any combination of magnesium carbonate, magnesium nitrate, magnesium chloride, magnesium phosphate, magnesium acetate, magnesium hydroxide, and magnesium fluoride; preferably, the magnesium source is one or any combination of magnesium carbonate, magnesium phosphate, magnesium acetate, and magnesium hydroxide;

[0024] Wherein, the phosphorus source is one or any combination of diammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium phosphate, magnesium phosphate, and phosphorus pentoxide; preferably, the phosphorus source is one or any combination of diammonium dihydrogen phosphate, ammonium phosphate, lithium phosphate, and magnesium phosphate;

[0025] Wherein, the Me source is one or any combination of Me oxides, hydroxides, fluorides, phosphates, sulfates, nitrates, acetates, and carbonates; preferably, the Me source is one or any combination of Me oxides, fluorides, acetates, and phosphates.

[0026] Wherein, in the preparation step S3: the dispersant is one or any combination of deionized water, ethanol, isopropanol, ketone, acetone, ethyl acetate, dimethylformamide and N-methylpyrrolidone; preferably, the dispersant is one or any combination of deionized water, ethanol, ethyl acetate, dimethylformamide and N-methylpyrrolidone.

[0027] Furthermore, in the preparation step S1: the mixing speed is 0-400 r / min, and the mixing time is 0-4 h; preferably, the ball milling mixing speed is 100-300 r / min, and the mixing time is 1-3 h; more preferably, the ball milling mixing speed is 100-300 r / min, and the mixing time is 1.5-2.5 h.

[0028] Furthermore, in the preparation step S2: the calcination temperature is 200-900°C, the calcination time is 1-20h, and the heating rate is 1-20°C / h; preferably, the calcination temperature is 300-600°C, the calcination time is 4-16h, and the heating rate is 5-15°C / h; more preferably, the calcination temperature is 400-500°C, the calcination time is 8-12h, and the heating rate is 8-12°C / h.

[0029] Further, in the preparation step S3: the ball milling speed of the ball milling mixing is 200-800 r / min, and the mixing time is 2-10 h; preferably, the ball milling mixing speed is 300-700 r / min, and the mixing time is 4-8 h; more preferably, the ball milling mixing speed is 400-600 r / min, and the mixing time is 5-7 h;

[0030] Furthermore, in the preparation step S3: the spray drying inlet air temperature is 150-300°C, the outlet air temperature is 80-120°C, and the feed frequency is 10-50Hz; preferably, the inlet air temperature is 180-260°C, the outlet air temperature is 90-110°C, and the feed frequency is 20-40Hz.

[0031] The present invention also provides the additive Li for coating the positive electrode material of a lithium battery a Mg b Me c (PO4) d Y e In the application of lithium battery positive electrode materials, the positive electrode material is mixed with 0-0.5wt% additive Li a Mg b Me c (PO4) d Y e Mix, sinter under air atmosphere, and sieve to obtain the additive Li a Mg b Me c (PO4) d Y e Coated positive electrode material.

[0032] The lithium battery positive electrode material includes one or more arbitrary combinations of ternary positive electrode materials, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate.

[0033] Preferably, the positive electrode material is preferably a ternary positive electrode material LiNi 0.65 Co 0.07 Mn 0.28 O2.

[0034] Preferably, the sintering temperature is 350° C.-400° C., and the sintering time is 5-15 hours.

[0035] Technical effect:

[0036] The present invention provides a Li-ion battery positive electrode material for coating a Mg b Me c (PO4) d Y eThe additive and its preparation method, the prepared lithium-rich additive coating can offset the irreversible lithium loss caused by the formation of SEI film during lithium ion insertion / deinsertion, so as to improve the initial total capacity of the battery. In addition, the additive can be used as Li + Conductor, can improve Li + The transmission rate on the surface of the positive electrode material improves the rate performance of the positive electrode material and effectively reduces the impedance of the electrode material. The anionic group of the additive can reduce the residual alkali of the positive electrode material, improve the high voltage stability of the lithium-ion positive electrode material, reduce the total alkali residue, and solve the problems of active lithium consumption caused by long cycles.

[0037] In addition, the preparation method provided by the present invention has low cost of raw materials, simple synthesis process and conditions, easy to implement, and environmentally friendly, and is suitable for large-scale industrial production.

[0038] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0040] Figure 1 This is the SEM image of the additive in the lithium battery positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0041] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0042] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0043] Example 1

[0044] A preparation method of an additive for coating anode materials of lithium batteries comprises the following steps:

[0045] (1) 178.2 g of lithium acetate, 262.9 g of magnesium phosphate, 248.7 g of cobalt trioxide, and 115.0 g of ammonium dihydrogen phosphate were added to a ball mill for mixing at a speed of 100 r / min for 1.5 h;

[0046] (2) calcining the obtained mixture in a muffle furnace at a calcination temperature of 800° C., a heating rate of 5° C. / h, and a calcination time of 12 h;

[0047] (3) The calcined mixture was added with anhydrous alcohol for ball milling at a speed of 500 r / min and a ball milling time of 6 h. The obtained slurry was spray dried at an inlet air temperature of 180° C., an outlet air temperature of 100° C. and a feed frequency of 30 Hz to obtain the coated additive LiMgPO4.

[0048] from Figure 1 From the SEM image of the additive of the corresponding prepared lithium battery positive electrode material, it can be seen that spherical lithium magnesium phosphate was obtained by ball milling, which increased the specific surface area of ​​lithium magnesium phosphate and was able to better coat the surface of the positive electrode material.

[0049] Example 2

[0050] An additive for coating anode materials of lithium batteries, the preparation method comprising the following steps:

[0051] (1) 35.1 g of lithium carbonate, 210.32 g of magnesium acetate, 5.10 g of aluminum oxide, 103.5 g of ammonium dihydrogen phosphate, and 5.19 g of lithium fluoride were added to a ball mill for mixing at a speed of 100 r / min for 1.5 h;

[0052] (2) calcining the obtained mixture in a muffle furnace at a calcination temperature of 800° C., a heating rate of 5° C. / h, and a calcination time of 12 h;

[0053] (3) The calcined mixture was added with anhydrous alcohol for ball milling at a speed of 500 r / min for 6 h. The obtained slurry was spray dried at an air inlet temperature of 180°C, an air outlet temperature of 100°C, and a feed frequency of 30 Hz to obtain the coated additive Li 1.15 Mg 0.8 Al 0.05 (PO4) 0.9 F 0.2 .

[0054] Example 3

[0055] A simple application of an additive for coating anode materials of lithium batteries comprises the following steps:

[0056] (1) 100g of Ni 0.65 Co 0.07 Mn 0.28 The (OH)2 ternary precursor and 38g lithium carbonate were placed in a muffle furnace, sintered at 880°C for 10h in an oxygen atmosphere, and then crushed using an ultrafine grinder and sieved to obtain an uncoated ternary positive electrode material;

[0057] (2) 100g of LiNi 0.65 Co 0.07 Mn 0.28 The O2 ternary positive electrode material and 0.5 g of the additive prepared in Example 1 were mixed in a mixer;

[0058] (3) The obtained mixture was placed in a muffle furnace, sintered at 460° C. in an air atmosphere for 8 h, and then sieved to obtain a ternary positive electrode material coated with lithium magnesium phosphate.

[0059] Example 4

[0060] A simple application of an additive for coating anode materials of lithium batteries comprises the following steps:

[0061] (1) 100g of Ni 0.65 Co 0.07 Mn 0.28 The (OH)2 ternary precursor and 38g lithium carbonate were placed in a muffle furnace, sintered at 880°C for 10h in an oxygen atmosphere, and then crushed using an ultrafine grinder and sieved to obtain an uncoated ternary positive electrode material;

[0062] (2) 100g of LiNi 0.65 Co 0.07 Mn 0.28 The O2 ternary positive electrode material and 0.5 g of the additive prepared in Example 2 were mixed in a mixer;

[0063] (3) The obtained mixture was placed in a muffle furnace, sintered at 460° C. in an air atmosphere for 8 h, and then sieved to obtain a ternary positive electrode material coated with lithium magnesium phosphate.

[0064] Comparative Example 1

[0065] (1) 100g of Ni 0.65 Co 0.07 Mn 0.28 The (OH)2 ternary precursor and 38 g of lithium carbonate were placed in a muffle furnace and sintered at 880°C for 10 h in an oxygen atmosphere. The resulting mixture was then crushed using an ultrafine grinder and sieved to obtain an uncoated ternary positive electrode material.

[0066] The test results of the physical characteristics of the additives for coating the positive electrode materials of lithium batteries prepared in the above Examples 1-4 and Comparative Example 1 are shown in Table 1 below.

[0067] Table 1 Physical characteristics test results of Examples 1-4 and Comparative Example 1

[0068]

[0069] The physical characteristics of the additives used for coating the positive electrode material of lithium batteries and the ternary positive electrode materials thereof in Examples 1-4 were tested; the results of Examples 3 and 4 and Comparative Example 1 showed that the lithium magnesium phosphate exhibited a large specific surface area, and the specific surface area of ​​the coated positive electrode material was also improved. In fact, by adding the additives for coating the positive electrode material of lithium batteries of the present invention, the specific surface area of ​​the obtained ternary positive electrode material was greatly improved.

[0070] The pH and total alkali test results of the coated lithium battery positive electrode materials prepared in the above Examples 3-4 and Comparative Example 1 are shown in Table 2 below.

[0071] Table 2 pH and total alkali test results of Examples 3-4 and Comparative Example 1

[0072] Test items Example 3 Example 4 Comparative Example 1 pH 11.56 11.53 11.68 Total alkali (ppm) 6194 6076 6751 Lithium carbonate (ppm) 3223 2751 3481 Lithium hydroxide (ppm) 1926 2156 2119

[0073] The results of Examples 3-4 and Comparative Example 1 show that the additives for coating the positive electrode materials of lithium batteries of the present invention can further reduce the total alkali residue on the surface of the ternary positive electrode materials, thereby lowering the pH value of the materials; under high temperature and high voltage, it can reduce gas production and improve high voltage and high temperature safety performance.

[0074] The impedance test results of the coated lithium battery positive electrode materials prepared in the above Examples 3-4 and Comparative Example 1 are shown in Table 3 below.

[0075] Table 3 Impedance test results of ternary positive electrode materials prepared in Examples 3-4 and Comparative Example 1

[0076] Rct / Ω Rw / Ω Example 3 8.541 9.357 Example 4 5.425 6.385 Comparative Example 1 7.934 9.992

[0077] The impedance test results provided by the above examples 3-4 and comparative example 1 show that the positive electrode material coated with LiMgPO4 increases the electron transfer internal resistance, but reduces the electron diffusion internal resistance. 1.15 Mg 0.8 Al 0.05 (PO4) 0.9 F 0.2 At the same time, the electron transfer internal resistance and diffusion internal resistance are reduced, and the ion transmission of the positive electrode material is improved.

[0078] The results of the charge-off test of the ternary positive electrode materials prepared in the above-mentioned Examples 3-4 and Comparative Example 1 are shown in Table 4 below.

[0079] Table 4 The results of the buckling test of the ternary positive electrode materials prepared in Examples 3-4 and Comparative Example 1

[0080]

[0081] Through the power-off test results provided in the above-mentioned Examples 3-4 and Comparative Example 1, the magnesium phosphate lithium coating of the present invention sacrifices the initial capacity of the ternary positive electrode material, but at the expense of a small amount of capacity, improves the cycle stability of the ternary positive electrode material. For example, the introduced Al, F, etc. can suppress the stability of the positive electrode material under high voltage and enhance the compatibility with the electrolyte.

[0082] In addition, the anionic groups of the additives can reduce the residual alkali in the positive electrode material and improve the high-voltage stability of the lithium-ion positive electrode material. At the same time, the lithium-rich additives can supplement part of the active lithium consumption caused by long cycles.

[0083] The present invention describes preferred embodiments and their effects; however, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, but not to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments can be modified, or some or all of the technical features can be replaced by equivalents without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. An additive for coating anode materials of lithium batteries, characterized in that: The additives include: Li a Mg b Me c (PO4) d Y e , where Me represents the doping transition metal element and Y represents the anion; Among them, 0<a≤1.5, 0<b≤1, 0≤c≤0.4, 0<d≤1, 0≤e≤0.

4.

2. An additive for coating a positive electrode material of a lithium battery as claimed in claim 1, further characterized in that the Me-doped transition metal element includes one or more elements of Al, V, Co, Cu, Nb, Mo, and Ti.

3. An additive for coating anode materials of lithium batteries as claimed in claim 1 or 2, further characterized in that the Y anion comprises Cl - 、F - 、NO3 - 、SO3 2- 、SO4 2- 、S2O8 2- 、SiO3 2- PO3 3- 、P2O7 4- One or more elements in .

4. An additive for coating anode materials of lithium batteries according to claim 1 or 2, characterized in that: Further, in the additive, 0.6≤a≤1.5, 0.5≤b≤1.0, 0.05≤c≤0.3, 0.5≤d≤1.0, 0.05≤c≤0.3; Furthermore, in the additive, 0.8≤a≤1.3, 0.8≤b≤1.0, 0.1≤c≤0.2, 0.8≤d≤1.0, 0.1≤c≤0.

2.

5. The method for preparing an additive for coating anode materials of lithium batteries according to any one of claims 1 to 4, characterized in that: The steps include: S1: mixing the lithium source, magnesium source, Me source and phosphorus source in proportion using a ball mill to obtain a first mixture; S2: Sinter the first mixture to obtain a sintered product Li a Mg b Me c (PO4) d Y e additive; S3: Add the obtained sintered product to a dispersant, mix by ball milling, and obtain the obtained slurry by spray drying and sieving to obtain additive powder.

6. A method for preparing an additive for coating a lithium battery positive electrode material as claimed in claim 5, characterized in that: The lithium source is one or any combination of lithium carbonate, lithium nitrate, lithium acetate, lithium chloride, lithium hydroxide, lithium fluoride, and lithium phosphate; preferably, the lithium source is one or any combination of lithium carbonate, lithium acetate, lithium hydroxide, and lithium fluoride; The magnesium source is one or any combination of magnesium carbonate, magnesium nitrate, magnesium chloride, magnesium phosphate, magnesium acetate, magnesium hydroxide, and magnesium fluoride; preferably, the magnesium source is one or any combination of magnesium carbonate, magnesium phosphate, magnesium acetate, and magnesium hydroxide; The phosphorus source is one or any combination of diammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium phosphate, magnesium phosphate, and phosphorus pentoxide; preferably, the phosphorus source is one or any combination of diammonium dihydrogen phosphate, ammonium phosphate, lithium phosphate, and magnesium phosphate; The Me source is one or any combination of Me oxides, hydroxides, fluorides, phosphates, sulfates, nitrates, acetates, and carbonates; preferably, the Me source is one or any combination of Me oxides, fluorides, acetates, and phosphates; The dispersant is one or any combination of deionized water, ethanol, isopropanol, ketone, acetone, ethyl acetate, dimethylformamide and N-methylpyrrolidone; preferably, the dispersant is one or any combination of deionized water, ethanol, ethyl acetate, dimethylformamide and N-methylpyrrolidone.

7. The method for preparing an additive for coating a positive electrode material of a lithium battery according to claim 5 or 6, further characterized in that in the preparation step S1: The ball mill mixing speed is 0-400r / min, and the mixing time is 0-4h; preferably, the ball mill mixing speed is 100-300r / min, and the mixing time is 1-3h; more preferably, the ball mill mixing speed is 100-300r / min, and the mixing time is 1.5-2.5h.

8. The method for preparing an additive for coating a positive electrode material of a lithium battery according to claim 5 or 6, further characterized in that in the preparation step S2: The calcination temperature is 200-900°C, the calcination time is 1-20h, and the heating rate is 1-20°C / h; preferably, the calcination temperature is 300-600°C, the calcination time is 4-16h, and the heating rate is 5-15°C / h; more preferably, the calcination temperature is 400-500°C, the calcination time is 8-12h, and the heating rate is 8-12°C / h.

9. The method for preparing an additive for coating a positive electrode material of a lithium battery according to claim 5 or 6, further characterized in that in the preparation step S3: The ball milling speed of the ball milling mixing is 200-800 r / min, and the mixing time is 2-10 h; preferably, the ball milling mixing speed is 300-700 r / min, and the mixing time is 4-8 h; more preferably, the ball milling mixing speed is 400-600 r / min, and the mixing time is 5-7 h; The spray drying has an inlet air temperature of 150-300°C, an outlet air temperature of 80-120°C, and a feed frequency of 10-50Hz; preferably, the inlet air temperature is 180-260°C, the outlet air temperature is 90-110°C, and the feed frequency is 20-40Hz.

10. A positive electrode material obtained by coating a positive electrode material of a lithium battery with an additive according to any one of claims 1 to 4, characterized in that: The lithium battery positive electrode material includes one or more arbitrary combinations of ternary positive electrode materials, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate.

Citation Information

Patent Citations

  • A cathode lithium supplement additive, its preparation method and application

    CN114220951B

  • Positive electrode lithium supplement additive and preparation method and application thereof

    CN118419984A

  • High-nickel ternary positive electrode material with low residual alkali, high specific capacity and high cycle stability and preparation method of high-nickel ternary positive electrode material

    CN118738357A

  • Coating modified positive electrode material, preparation method of coating modified positive electrode material, positive electrode plate, lithium ion battery and power utilization device

    CN118763207A